Analysis of Investment Attractiveness of Water Supply Enterprises - Toshmuxamadovna, Abdujaborova Mamura (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the role of water supply companies in the economy, the direction of the analysis of their investment attractiveness and the importance of increasing it, the approaches of foreign scientists in the study of investment attractiveness of the industry. In the analysis of the investment attractiveness of water supply enterprises, the use of financial ratios, their description taking into account the characteristics of enterprises in the sector, the aspects that need to be considered in order to achieve a positive view of financial ratios. There are also definitions of the concept of “investment attractiveness” given by economists, the purpose, tasks, stages, directions of the analysis of investment attractiveness of enterprises.